Management of diabetic foot ulcers in a teaching hospital - Sade, Rajkumar; Jatothu, Dasharadha; Taruni, .; Sade, Kirthana; Pyadala, Nagababu (International Surgery Journal, 2017)
Background: Diabetic foot ulcers (DFUs) are major public health problem, especially in developing countries. Still now management of diabetic foot ulcer is the major challenge for surgeons. Methods: A prospective study was done at Kamineni Institute of Medical Sciences, Narketpally; from February 2014 to January 2017. All the collected data was analyzed by the SPSS 20.0 software. Results: A total of 350 DFUs patients was included in this study. Among all of them 77.14% were male and 22.86% were female. Most common age group with DFUs was 40-60 years. All the patients had type 2 diabetes mellitus. The majority of patients were presented foot ulcers between 4 weeks to 32 weeks. 18% patients had previous history of DFUs and 11.14% had previous amputation. The forefoot was commonly affected in 48.3% of cases. Neuropathic ulcers were the most common type of DFUs in 50.6% of cases. Wagner’s stage 3, 4 and 5 ulcers were the most common at 20.86%, 28% and 22% respectively. 52.86% patients were treated surgically. Lower limb amputation was the most common surgical procedure performed in 60% of cases. The complication rate was (49.7%) and surgical site infection was the most common complication (34.8%). 60% of cultures had polymicrobial growth and Staphylococcus aureus (53.3%) was the most common microorganism isolated. Most of the microorganisms isolated showed multi drug resistance to commonly used antibiotics except for Carbapenems group drugs (sensitivity 100%). The hospital stay was ranged between 15-116 days. Mortality rate was 9.4%. Conclusions: Diabetic foot ulcer is the major cause of morbidity and mortality among patients with diabetes mellitus. A proper education on foot care and appropriate foot ware, good sugar level control and early surgical intervention is needed to decrease the morbidity and mortality among diabetic foot ulcer patients.